Development of real‐time loop‐mediated isothermal amplification (RealAmp) method for sensitive and rapid detection of pathogenic and nonpathogenic Leptospira. (13th January 2019) - Monica, N.I.; Rathinasabapathi, P.; Ramya, M.
Abstract: Leptospirosis is a zoonotic disease that is spread through water contaminated with the spirochete Leptospira . In our study, RealAmp (real‐time loop‐mediated isothermal amplification) was developed to distinguish between pathogenic and nonpathogenic Leptospira spp. Melt curve analysis of RealAmp showed two distinct melt curves for pathogenic and nonpathogenic Leptospira spp with a Tm value of 90 ± 2 and 88 ± 2°C. The sensitivity of the developed method is as low as 1 pg μl −1 of Leptospira DNA. Specificity was achieved to distinguish Leptospira species using the marker genes ( lipL32 and lipL21 ). Different environmental water samples collected from cattle shelter, pisciculture and stagnant water were tested using this RealAmp method. Pisciculture water samples were found to be highly contaminated with both pathogenic and nonpathogenic Leptospira spp (50%), followed by cattle shelter and stagnant water samples (15%). Significance and Impact of the Study: The occurrence of pathogenic Leptospira in the environment is a threat to humans and animals. Molecular‐based differentiation of the pathogenic and nonpathogenic Leptospria is essential for environmental monitoring; however, the currently available detection methods fail to distinguish between these species. We report here a real‐time loop‐mediated isothermal amplification‐based method that differentiates between the pathogenic and nonpathogenic Leptospira based on the melt curve analysis of the marker genes lipL32 and lipL21 . The method was successfully tested with a variety of environmental water samples to study the prevalence of Leptospira in the environment. Abstract : Significance and Impact of the Study: The occurrence of pathogenic Leptospira in the environment is a threat to humans and animals. Molecular‐based differentiation of the pathogenic and nonpathogenic Leptospria is essential for environmental monitoring; however, the currently available detection methods fail to distinguish between these species. We report here a real‐time loop‐mediated isothermal amplification‐based method that differentiates between the pathogenic and nonpathogenic Leptospira based on the melt curve analysis of the marker genes lipL32 and lipL21 . The method was successfully tested with a variety of environmental water samples to study the prevalence of Leptospira in the environment.